Impact of the Post Pandemic on College Student’ Lifestyles - Huamán-Romaní, Yersi-Luis; Garrido-Arismendis , Juan-Jesús; Manrique-Nugent , Manuel-Alberto-Luis; Serna-Silva, Giovanna-Jackeline; Vásquez-Alburqueque, Iris-Liliana; Cahuana Lipa , Rocio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The pandemic motivated nutrition and healthy living to maintain a healthy lifestyle. The objective is to analyze and describe the perspectives of post-pandemic lifestyles of university students, using the quantitative cross-sectional method with non-probabilistic sampling and survey that measures the nutritional level and level of physical activities, 1033 university students participated. The results showed that the measurement instrument in the Peruvian context is acceptable and that the level of lifestyle is moderate. In conclusion, nutritional policies and physical activities should be considered in universities so that university students practice a healthy lifestyle and take care of their health.